Does Knowledge Affect the Attitude of Fertile Aged Women in Visual Inspection with Acetic Acid Examination? A cross-sectional study: Apakah Pengetahuan Mempengaruhi Perilaku Wanita Berusia Subur pada Pemeriksaan Inspeksi Visual Asetat? Sebuah Studi Potong Lintang - Christy Hanudji; Eddy Suparman; Joice M. M. Sondakh (Indonesian Socety of Obstetrics and Gynecology, 2021)
Objective: To find out the relationship between knowledge and attitudes of fertile aged women with IVA examination behaviour at Bitung Barat Public Health Center in Bitung City.Method: This was a cross-sectional study. Samples of 145 fertile aged women in area Bitung Barat Public Health Center Bitung city.Results: Of the 145 respondents, the highest group had sufficient and good knowledge. The highest percentage is respondents who have sufficient knowledge with a percentage of 44.14%. The attitude towards the IVA examination was assessed as good as 122 people (84.14%). The number of respondents who did not do an IVA examination is 94 people (64.83%) more than respondents who did not do an IVA examination that is 51 people (35.17%). Based on the results of statistical tests it is known that the significance value of p = 0.000. The attitude of women of childbearing age is good then the behaviour of IVA examination is also good with the results of statistical tests known that the significance value p = 0.001.Conclusions: Respondents with good IVA examination behaviour have good knowledge and attitude.Keywords: attitude, behaviour, IVA examination, knowledge. Abstrak Tujuan: Mengetahui hubungan antara pengetahuan dan sikap perempuan usia subur dengan perilaku pemeriksaan IVA di Puskesmas Bitung Barat Kota Bitung.Metode: Metode penelitian berupa analitik observasional dengan rencangan potong lintang. Sampel sebesar 145 perempuan usia subur di wilayah Puskemas Bitung Barat Kota Bitung.Hasil: Dari 145 responden, kelompok tertinggi memiliki pengetahuan yang cukup dan baik. Persentase tertinggi yaitu responden yang memiliki pengetahuan cukup dengan persentase 44,14%. Sikap terhadap pemeriksaan IVA dinilai baik yaitu sebanyak 122 orang (84,14%). Jumlah responden yang tidak melakukan pemeriksaan IVA yaitu 94 orang (64,83%) lebih banyak dari responden yang tidak melakukan pemeriksaan IVA yaitu 51 orang(35,17%). Berdasarkan hasil uji statistik diketahui bahwa nilai signifikansi p= 0,000. Sikap perempuan usia subur yang baik maka perilaku pemeriksaan IVA juga baik dengan hasil uji statistik diketahui bahwa nilai signifikansi p= 0,001.Kesimpulan: Responden dangan perilaku pemeriksaan IVA yang baik memiliki pengetahuan dan sikap yang baik.Kata kunci: pengetahuan, pemeriksaan IVA, perilaku, sikap..